Analisis Laporan Realisasi Anggaran Belanja Pada Dinas Koperasi Dan UMKM Kota Ambon - Asrida, Wa; Sandanafu, Sally P.; Kempa, Ester Stevanny (Journal of Applied Accounting, 2024)
This research aims to analyze the budget realization report at the Ambon City Cooperatives and UMKM Service. Expenditure is a component of budget realization that is given great attention, therefore it is necessary to carry out an analysis of expenditure realization to be used as an evaluation to increase expenditure realization in the following year. This research is a quantitative descriptive research. The data used in the analysis is the 2019-2021 Expenditure Budget Realization report. The analysis technique used is in the form of documentation and is analyzed using spending variance analysis, spending harmony analysis, and spending efficiency analysis. The research results show that spending at the City Cooperative and UMKM Department, seen from the spending variance, is generally said to be good because this analysis is categorized as a favorable variance, meaning that the realization is smaller than the budget. The spending harmony analysis is considered unbalanced because some of the funds are allocated for operational spending and only a few percent are allocated for capital spending. The analysis of spending efficiency in general has performed well and it can be said that the Ambon City Cooperatives and UMKM Department has carried out spending efficiency.